Constructing bifunctional Co3O4@Ni3S2 as pair of electrooxidations catalysts with superior photoelectrocatalytic efficiency for water purification. Issue 3 (June 2022) - Jiang, Zeqi; Li, Wenfeng; Liu, Xinghui; Han, Huibin; Song, Yu; Fu, Yinghuan; Ma, Chun; Wang, Guowen; Ma, Hongchao
Abstract: Finding a bifunctional heterostructure catalyst that can act as a pair of electrooxidations to decompose refractory organic dyes in wastewater is an important issue. Herein, we succeeded in preparing a Co3 O4 @Ni3 S2 heterostructure by the two-step hydrothermal method as promising bifunctional catalysts that function simultaneously as the anode and cathode. Remarkably, the optimized bifunctional Co3 O4 @Ni3 S2 -3.0 electrodes exhibit a degradation rate of ~ 95% and acceptable stability for practical usage, which can be attributed to its low Tafel slope, large electrochemically active surface area, and low charge transfer resistance. Free radical capture experiments using auxiliary probe molecular fluorescence experiments suggest that the Z-scheme heterostructure of Co3 O4 @Ni3 S2 -3.0 is proposed to promote charge separation and produce the main active species. The rational design of this work--a new strategy for establishing a highly efficient bifunctional pair of electrooxidation heterostructure catalysts of Co3 O4 @Ni3 S2 -3.0 with a Z-scheme band structure—will lead to other catalysts designs. Graphical Abstract: ga1 Highlights: Z‑scheme Co3 O4 @Ni3 S2 as pair of electrooxidations catalysts was synthesized. it exhibited excellent reactive brilliant blue KN-R degradation capabilities. The synergistic photoelectrocatalytic effect leads to efficient dye degradation. Achieved a decomposition efficiency of ~95% with excellent stability.